Geometric Optimisation of Earth Retaining Quay Walls for the Marine Environment through the use of Ground Anchors - Green, Alexander Malcolm (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.